E-Marketing, Keragaman Produk dan Keputusan Pembelian (Studi Pada UKM Batik Surya 26 Kabupaten Tuban) - M. Yudis Sugianto; Fathor AS (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The purpose of this study is to influence, e-marketing and product diversity in UKM Batik Surya 26 Tuban Regency, either partially or simultaneously on purchasing decisions. This research was conducted using quantitative descriptive methods. The sampling technique used was non-probability sampling with the incidental sampling method used as a sampling method, in order to obtain a sample of 97 people and hypothesis testing using multiple linear regression analysis. The conclusion of the results of this study is that e-marketing partially has a significant effect on purchasing decisions, partial product diversity has a significant effect on purchasing decisions, and e-marketing and product diversity simultaneously has a significant effect on purchasing decisions.